Self-Evaluation of Jurnal Informatika Sunan Kalijaga (JISKa): Perspectives of Reviewers and Authors - Wonoseto, Muhammad Galih; Gunawan, Eko Hadi; Minati, Sekar; Nuruzzaman, Muhammad Taufiq (IJID (International Journal on Informatics for Development), 2021)
The success of JISKa is inseparable from the role of reviewers and authors. Unfortunately, JISKa had never been assessed or evaluated by reviewers and authors despite the fact that assessment from the reviewers and authors would be valuable feedback for JISKa’s self-evaluation. Therefore, survey-based research has recently been conducted to assess JISKa’s performance using the User Acceptance Test of OJS version 2.4.8.0. This study used a survey method to obtain an assessment and evaluation from reviewers and authors related to JISKa.The respondents in this study consist of 68 authors and 26 reviewers. The result of this study stated that 91.2% of the authors and 84.6% of reviewers are satisfied with JISKa. A percentage number of 100% of writers and reviewers wants JISKa to raise its level of Sinta accreditation. This accreditation is awarded in 2018 and will end in 2023. JISKa is now on Sinta 4.The JISKa website appearance looks good and easy to use. The dashboard on the JISKa page is user-friendly for the author. However, the current version of JISKa OJS 2.4.8.0 needs to be upgraded to OJS version 3. There are some points for the future consideration of JISKa: JISKa needs to promote itself more, upgrade the OJS version, and provide the reviewers with certificates of appreciation for future consideration.